2005
DOI: 10.1210/jc.2004-2140
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapeutic Strategy for Medullary Thyroid Cancer Based on Radioiodine Therapy following Tissue-Specific Sodium Iodide Symporter Gene Expression

Abstract: A therapeutic effect of 131-I has been demonstrated in MTC cells after induction of tissue-specific iodide uptake activity by calcitonin promoter-directed hNIS expression. This study demonstrates the potential of NIS as a therapeutic gene, allowing radioiodine therapy of MTC after tissue-specific NIS gene transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 47 publications
0
33
0
3
Order By: Relevance
“…Differentiated thyroid carcinoma with hNIS expression responds to 131 I therapy; however, most ATCs respond poorly to this therapy because of their inability to accumulate iodine (26). Several investigators have suggested the use of radioiodine therapy after exogenous hNIS gene expression in anaplastic thyroid carcinoma or other nonthyroid cancers that lack hNIS expression (19)(20)(21)27,28). These results suggest that hNIS gene transfer may be used for cancer therapy by restoring or inducing radioiodine uptake in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated thyroid carcinoma with hNIS expression responds to 131 I therapy; however, most ATCs respond poorly to this therapy because of their inability to accumulate iodine (26). Several investigators have suggested the use of radioiodine therapy after exogenous hNIS gene expression in anaplastic thyroid carcinoma or other nonthyroid cancers that lack hNIS expression (19)(20)(21)27,28). These results suggest that hNIS gene transfer may be used for cancer therapy by restoring or inducing radioiodine uptake in various cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clonogenic survival was reduced in the NIS-expressing QGP and Bon1 cells by 99.8 and 98.8%, respectively, after incubation with 100 µCi/ml of 131 I [144]. Cengic et al (2005) assessed the feasibility of radioiodide therapy of medullary thyroid cancer (MTC) after NIS gene transfer using the tissue-specific calcitonin promoter to target hNIS gene expression to MTC cells. MTC cells were stably transfected with an expression vector, in which hNIS cDNA was coupled to the calcitonin promoter.…”
Section: Preclinical Studies Of Nis Gene Transfer By Replication-defementioning
confidence: 99%
“…The stably transfected HCT116 cells concentrated 125 I about 10-fold in vitro without evidence of iodide organification. Furthermore, 95% of stably transfected HCT116 cells were killed by exposure to 131 I, while only about 5% of NIS-negative control cells were killed [146]. reported on a study of in vivo NIS gene transfer followed by radioiodide imaging and treatment in a breast cancer model.…”
Section: Preclinical Studies Of Nis Gene Transfer By Replication-defementioning
confidence: 99%
“…These findings indicate that NIS gene delivery can lead to sufficient NIS activity for radioiodide therapeutic use and also that iodide organification is not a fundamental step for radioiodine effectiveness to occur. hNIS gene transfer has also been tested using the calcitonin-promoter to target NIS gene expression to medullary thyroid cancer cells (97). After NIS-gene transfer, these cells were able express functional NIS and to significantly uptake iodide.…”
Section: Nis Gene Transfer For Cancer Managementmentioning
confidence: 99%